Qualitative Analysis of Preventing Factors for Extramarital Relationships in Married Couples - Babak Eslamzadeh; Fatemeh Sadeghi; Masoume Esmaeily (Kerman University of Medical Sciences, 2019)
Introduction: Extramarital relationships is one of the most important factors threatening marriage between couples. As understanding the preventing factors has a very high value in maintaining the quality of marriage, therefore, the present study was conducted to explain the experiences of married couples about the preventing factors for extramarital relationships. Method: This qualitative study was conducted using a phenomenological approach. The samples were selected from couples who got married one year ago, for this purpose, 19 couples were selected using purposeful sampling. Data were collected using semi-structured in-depth interviews until data saturation. Data were analyzed using coding technique (Strauss and Corbin) with a focus on the theoretical and purposeful sampling, constant comparison, encoding and concept development. Results: In this study, three categories of factors including internal factors (self-awareness, spirituality, and fear), external factors (context, culture, foresight, and family), and relational factors (spiritual intimacy and relational intimacy) were identified as the effective preventing factors for extramarital relationships. Conclusion: It seems necessary to determine the factors threatening the comfort and stability of the family as the cornerstone of society. In the present study, it was found that a set of factors including internal, external, and relational factors, protected couples from extramarital relationships. The results of this study can be used in the development of preventive and therapeutic programs in the areas of marital infidelity.